2020
DOI: 10.1186/s12864-020-6587-z
|View full text |Cite|
|
Sign up to set email alerts
|

RNA-Seq and secondary metabolite analyses reveal a putative defence-transcriptome in Norway spruce (Picea abies) against needle bladder rust (Chrysomyxa rhododendri) infection

Abstract: Background Norway spruce trees in subalpine forests frequently face infections by the needle rust fungus Chrysomyxa rhododendri, which causes significant growth decline and increased mortality of young trees. Yet, it is unknown whether trees actively respond to fungal attack by activating molecular defence responses and/or respective gene expression. Results Here, we report results from an infection experiment, in which the transcriptomes (via RNA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
38
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(45 citation statements)
references
References 89 publications
7
38
0
Order By: Relevance
“…In rust fungi, different approaches are used in the functional characterization of these proteins, including analysis of subcellular localization in planta[19,25,28,30,31], infection assays in true host or in a model plant, and induction/repression of plant cell death[19,30,36,37]. The transcriptome or metabolome of the host in responses to the pathogen are frequently evaluated[38][39][40][41][42][43], but the assessment of the role of individual CEs in these processes is not easily measured and seldom analyzed[22,44].Here we investigated 14 CEs from Melampsora larici-populina by evaluating their individual impact on the transcriptome and metabolome of stable transgenic Arabidopsis plants. By studying the impact of several individual CEs, we were able to compare patterns of gene and metabolite deregulation.…”
mentioning
confidence: 99%
“…In rust fungi, different approaches are used in the functional characterization of these proteins, including analysis of subcellular localization in planta[19,25,28,30,31], infection assays in true host or in a model plant, and induction/repression of plant cell death[19,30,36,37]. The transcriptome or metabolome of the host in responses to the pathogen are frequently evaluated[38][39][40][41][42][43], but the assessment of the role of individual CEs in these processes is not easily measured and seldom analyzed[22,44].Here we investigated 14 CEs from Melampsora larici-populina by evaluating their individual impact on the transcriptome and metabolome of stable transgenic Arabidopsis plants. By studying the impact of several individual CEs, we were able to compare patterns of gene and metabolite deregulation.…”
mentioning
confidence: 99%
“…In rust fungi, different approaches are used in the functional characterization of these proteins, including analysis of subcellular localization in planta [ 22 , 27 , 28 , 30 , 50 ], infection assays in true host or in a model plant, and induction/repression of plant cell death [ 22 , 30 , 57 , 58 ]. The transcriptome or metabolome of the host in responses to the pathogen are frequently evaluated [ 59 , 60 , 61 , 62 , 63 , 64 ], but the assessment of the role of individual CEs in these processes is not easily measured and seldom analyzed [ 24 , 65 ]. Here, we investigated 14 CEs from Melampsora larici-populina by evaluating their individual impact on the transcriptome and metabolome of stable transgenic Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…GO annotation showed that 4,341 DEGs belonging to cellular, bio-chemical and molecular components. Recent study of Norway spruce tree's transcriptome showed involvement of molecular function, biological process but no cellular component term during needle bladder rust, suggesting a variable responses of DB infection 46 . During DB infection, it was noted that 73 DEGs were related to plant-pathogen interaction, suggesting a post-herbivory genetic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, CaM/CML protein family regulate cellular responses to pathogenic induced HR responses in grapevine 54 . Activation of HR responses in DB infection could have played role in reducing infection caused by extricating cell death in neighboring cells 46 . A similar conclusion was also revealed by Trujillo-Moya et al 46 Norway spruce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation